The Induction of Noble Rot (Botrytis cinerea) Infection during Postharvest Withering Changes the Metabolome of Grapevine Berries (Vitis vinifera L., cv. Garganega) - Negri, Stefano; Lovato, Arianna; Boscaini, Filippo; Salvetti, Elisa; Torriani, Sandra; Commisso, Mauro; Danzi, Roberta; Ugliano, Maurizio; Polverari, Annalisa; Tornielli, Giovanni B.; Guzzo, Flavia (Frontiers in Plant Science, 2017)
The natural or induced development of noble rot caused by the fungus Botrytis cinerea during the late stages of grapevine (Vitis vinifera L.) berry ripening is used in some traditional viticulture areas to produce high-quality wines such as Sauternes and Tokaji. In this research, we wanted to verify if by changing the environmental conditions during post-harvest withering we could induce the noble rot development on harvested berries in order to positively change the wine produced from withered Garganega berries. Therefore, we exposed the berries to postharvest withering under normal or artificially humid conditions, the latter to induce noble rot. The presence of noble rot symptoms was associated with the development of B. cinerea in the berries maintained under humid conditions. The composition of infected and non-infected berries was investigated by untargeted metabolomics using liquid chromatography/mass spectrometry. We also explored the effects of the two withering methods on the abundance of volatile organic compounds in wine by yeast-inoculated micro-fermentation followed by targeted gas chromatography/mass spectrometry. These experiments revealed significant metabolic differences between berries withered under normal and humid conditions, indicating that noble rot affects berry metabolism and composition. As well as well-known botrytization markers, we detected two novel lipids that have not been observed before in berries infected with noble rot. Unraveling the specific metabolic profile of berries infected with noble rot may help to determine the compounds responsible for the organoleptic quality traits of botrytized Garganega wines.